IMPLEMENTASI KEBIJAKAN PERATURAN WALIKOTA TEGAL NO 6 TAHUN 2013 TENTANG PENYELENGGARAAN PELAYANAN INFORMASI PUBLIK DI LINGKUNGAN PEMERINTAH KOTA TEGAL (Kajian Pasal 6 Informasi Yang Wajib Disediakan Dan Diumumkan Badan Publik) - Ariani, Trinanda Meinar; Suwitri, Sri (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
There are still a delayed public information service in Tegal City that is not in accordance with the applicable regulation by the relevant agencies to be the background of this research. The objective of the research is to describe and analyze the implementation of public information service policy in Tegal City Government. Identify and analyze related to obstacle factor of policy of public information service in environment of Tegal City Government. Using the implementation theory of Daniel A. Mazmanian and Paul A. Sabatier and Van Meter and Van Horn with variable characteristics of policy, resources, and characteristics of implementing agents. Techniques of data collection using observation, interviews, and documentation. Informant selection using snowball technique. The result of the research shows that the obstacles of policy implementation are allocation of fund resources, human resources condition, facilities and infrastructure facilities, support of bureaucracy structure and communication relationship in internal bureaucracy. Recommendation given is the need to strengthen the vision and mission in the internal bureaucracy, budget preparation, planned human resource planning and improve the pattern of communication relations in the internal bureaucracy.